Interfertility between Armillaria cepistipes and A. sinapina - Bérubé, J.A.; Dessureault, M.; Berthelay, S.; Guillaumin, J.-J. (Phytoprotection, 1996)
European strains of Armillaria cepistipes were reported to be interfertile with strains from three American Armillaria species known as North American Biological Species (NABS) V (A sinapina), NABS X and NABS XI. Such interfertility between species raises some doubts about using different Latin binomials for species capable of mating. This interfertility was reinvestigated by mating 24 haploid isolates of European A cepistipes with 23 isolates of A sinapinafrom North America and Asia. Individual pairings were independently performed at least once at Universite Laval, Canada and at INRA Clermont-Ferrand, France. From the 420 interspecific pairings performed at Laval, two were positive and seven were ambiguous for a total of 2.1% of all the pairings. From the 506 pairings made at Clermont-Ferrand, 10 were positive and 24 were ambiguous for a total of 6.7%. The differences in the pairing results may be explained by incubation temperatures, and the different types and concentrations of malt extract used at each laboratory. The low levels of interfertility found between A. cepistipes and A. sinapina may result from the absence of genetic barriers that are usually present between sympatric species. This low level of interfertility reflects differences in morphology, distribution, and habitat for these two species of Armillaria and this supports the retention of different species denominations.